Analisis Kinerja Portofolio dan Kemampuan Manajer Investasi Reksa Dana Syariah di Indonesia - Muchtiari, Andi Rini; Mohamad, Roni (Madani: Jurnal Pengabdian Ilmiah, 2020)
This paper aims to analyze the performance of Islamic equity funds in Indonesia, which is indicated by the ability of the Mutual Fund to choose stocks that can provide greater returns than market returns. This study uses Jensen's Measure (α). The Jensen measurement aims to calculate the rate of return above the CAPM by looking at beta and the rate of return above the market (the measure of differential return) by adding elements of macroeconomic variables such as the Rupiah exchange rate and inflation in the analysis of the performance of Islamic mutual funds. The results of regression testing prove that investment managers in Islamic mutual funds have the ability to sell (buy) shares at the right time, but because the relationship between mutual fund portfolios and market shares is very sensitive and has a negative beta, the investment manager's ability to use transaction time is not able to create a portfolio of mutual funds have.